PHENOTYPIC CHARACTERIZATION OF WHEAT SELECTED LINES FOR RESISTANCE AGAINST LEAF STRIPE AND STEM RUST THROUGH PHENOTYPIC MARKERS APPLICATION - M. Hussain; M. A. Khan; M. Hussain; N. Javed; I. Khaliq (Journal of Animal and Plant Sciences, 2016)
Leaf, stripe and stem rust are considered one of the most important diseases of wheat in Pakistan. The use of rust resistant varieties is the most economical and environment friendly way to reduce losses due to rust diseases. For this purpose a study was planned to combine genes for enhancing rust resistance and high yield potential in wheat.The experiments for identification of durable rust resistance genes i.e. Sr2/Yr30, Lr34/Yr18, Lr46/Yr29 on the basis of phenotypic markers like pseudo black chaff (Pbc) and leaf tip necrosis (Ltn1 & Ltn2) were conducted in augmented design during the years 2010-11 and 2011-12 at Wheat Research Institute, Faisalabad and Summar Agricultural Research Station, Kaghan. Total 750 head rows were selected from F6 generation and planted at SARS, Kaghan. The outstanding 345 lines were selected and planted for further evaluation and on the basis of rust reactions, phenotypic uniformity and high yield under the field conditions, 220 lines were selected for further testing. The results indicate that among 220 entries, 67 entries showed Lr34/Yr18, 23 entries showed Lr46/Yr29 and 62 entries showed Sr2/Yr30 genes combination. While in yield testing, among test entries, 99 entries were found to be high yielding ranging from 3973-4786 kg/ha. From the study, it is concluded that fourteen test entries i.e. V-11211,V-11212, V-11218, V-11227, V-11262, V-11288, V-11296, V-11304, V-11308, V-11319, V-11338, V-11353, V-11365 and V-11396 are the most prominent lines because these lines showed the combination of all three slow rusting genes as well as high yield potential. These selected genotypes will be very useful for the wheat breeders and pathologist of the country in planning of future hybridization program.
Keywords: Breeding; resistance; slow rusting genes; phenotypic markers; Triticum aestivum; leaf and stripe rust